AD, Volume 27, n° 1 & 2, 2002 - Full Issue - Journal System, (Africa Development, 2002)
Contents Editorial Francis B. Nyamnjoh ...............................i La Gouvernance économique: Quelles incidences sur le développement au Congo-Brazzaville? Mathias Marie Adrien Ndinga ...............:................1 Economie Refonns and the Malian Economy Yves Bourdet ....................................25 La sécmité foncière sur les périmètres irrigués du Burkina Faso: Le cas de la vallée du Sourou Basga Emile Dialla ..............................62 Le Source de financement des investissements de la PME: Une étude empirique sur la donnée Sénégalaise Mahmoudou Bocar Sail...........................84 Extension Needs ofWomen Cassava Fanners in Igueben and Esan Northeast local Govemment Areas of Edo State, Nigeria Eddy Onemolease ..................................116 An Empirical Analysis of Food Insecurity in Ethiopia: The Case of North Wello G. Ramakrishna & Assefa Demeke ..........................127 Pratiques et logiques de l'épargne collective chez les migrants maliens et sénégalaisen France Seydi Ababacar Dieng .................................144 Démocratisation, exacerbation identitaire et rivalités ethniques: Le Cas du Sud-Cameroun BelingaJoseph-Marie Zambo ...............................175 The Political Economy of Terrorism Adekunle Amuwo .............................205 Alternative Modes of Financing Higher Education in Nigeria and Implications for University Govemance Olabisi I. Aina................................236 Comparison Between School Effectiveness Characteristics and Classroom Instruction Strategies in the United States and Nigeria David A. Adewuyi............................262 Book Review: Ifi Amadiume, Daughters of the Goddess, Daughters of lmperiaHsm: Afiican Women Struggle for Culture, Power and Democracy, (London: Zed Books Ltd, 2000), xviii+300 pp. Hannington Ochwada ...........................288